2012
DOI: 10.1007/s12291-012-0258-z
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm of Serum Cortisol in Female Patients with Fibromyalgia Syndrome

Abstract: Fibromyalgia syndrome (FMS) patients have disturbed sleep patterns which may lead to altered circadian rhythm in serum cortisol secretion. The aim of this study was to assess circadian changes, if any, in serum cortisol levels in female patients with FMS. Cortisol levels were estimated every 6 h during 24 h period; in 40 female patients satisfying ACR criteria for FMS (Age 36.4 ± 9.9), and 40 healthy females without FMS (Age 33.8 ± 11.1). A significant difference in the night time serum cortisol level was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…It should be pointed out that depending on when CRH is released and where in the brain, it may not necessarily activate the hypothalamic-pituitary-adrenal axis and lead to increased serum cortisol. This may be the reason why morning serum cortisol is not different between FMS patients and controls, but evening cortisol is actually increased in FMS patients (Fatima et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…It should be pointed out that depending on when CRH is released and where in the brain, it may not necessarily activate the hypothalamic-pituitary-adrenal axis and lead to increased serum cortisol. This may be the reason why morning serum cortisol is not different between FMS patients and controls, but evening cortisol is actually increased in FMS patients (Fatima et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…We collected blood at the same time of day for all participants to avoid the effects of daily variations in the level of NO and cortisol (Fatima et al, 2013;Kanabrocki et al, 2001). After blood collection, we allowed the tubes to stand at room temperature for 30 min until the blood clotted.…”
Section: Blood Collection and Preparation Of Blood Samplesmentioning
confidence: 99%
“…Since the sleep pattern is disrupted in women with FMS, it may lead to some changes in the circadian rhythm and disrupt the serum cortisol secretion. The circadian oscillation of the cortisol is abnormal in women with FMS [10][11][12]. A study by Fatima et al [11] found the cortisol level in women with FMS to be significantly higher at night.…”
Section: Discussionmentioning
confidence: 97%
“…Chronic pain and stress-related deviations in hormonal secretion occur in patients with FMS. Hypothalamiccorticotrophin-releasing hormone (CRH) neurons are activated in the central nervous system depending on chronic stress [10][11][12].…”
Section: Discussionmentioning
confidence: 99%